Tetramethylpyrazine: A Review of Its Antitumor Potential and Mechanisms - Yang, Shaojie; Wu, Shuodong; Dai, Wanlin; Pang, Liwei; Xie, Yaofeng; Ren, Tengqi; Zhang, Xiaolin; Bi, Shiyuan; Zheng, Yuting; Wang, Jingnan; Sun, Yang; Zheng, Zhuyuan; et al. (Frontiers in Pharmacology, 2021)
Cancer remains a major public health threat. The mitigation of the associated morbidity and mortality remains a major research focus. From a molecular biological perspective, cancer is defined as uncontrolled cell division and abnormal cell growth caused by various gene mutations. Therefore, there remains an urgent need to develop safe and effective antitumor drugs. The antitumor effect of plant extracts, which are characterized by relatively low toxicity and adverse effect, has attracted significant attention. For example, increasing attention has been paid to the antitumor effects of tetramethylpyrazine (TMP), the active component of the Chinese medicine Chuanqiong, which can affect tumor cell proliferation, apoptosis, invasion, metastasis, and angiogenesis, as well as reverse chemotherapeutic resistance in neoplasms, thereby triggering antitumor effects. Moreover, TMP can be used in combination with chemotherapeutic agents to enhance their effects and reduce the side effect associated with chemotherapy. Herein, we review the antitumor effects of TMP to provide a theoretical basis and foundation for the further exploration of its underlying antitumor mechanisms and promoting its clinical application.